The TNBS-induced colitis animal model: An overview. (November 2016) - Antoniou, Efstathios; Margonis, Georgios Antonios; Angelou, Anastasios; Pikouli, Anastasia; Argiri, Paraskevi; Karavokyros, Ioannis; Papalois, Apostolos; Pikoulis, Emmanouil
Abstract: Background: Despite recent advances the pathogenesis of Crohn's disease remains incompletely understood. A variety of animal models have been utilized in an effort to provide further insights and develop more therapeutic options. In order to simulate, to an extent, the pathogenesis and the clinical course of the disease, TNBS induced colitis is often used. Various approaches for inducing TNBS -colitis have been described in the literature. Methods/results: In this review, we sought to present the animal model of TNBS induced colitis and outline the pathogenesis, pathophysiology, clinical course and pathological characteristics of the model. Furthermore, we describe the differences among those protocols regarding types of animals and colitis induction. Data sources: The MEDLINE database was thoroughly searched using the keywords: TNBS, colitis, Crohn's disease, animal model. Two investigators independently reviewed the abstracts and appropriate articles were included in this review. Additional articles were gathered and evaluated. Conclusion: The aim of this study was to thoroughly present an updated review of the TNBS-induced colitis protocols that are implemented by researchers. Highlights: We sought to present the animal model of TNBS induced colitis and outline the pathogenesis, pathophysiology, clinical course and pathological characteristics of the model. Furthermore, we describe the differences among those protocols regarding types of animals and colitis induction. The MEDLINE database was thoroughly searched using the keywords: TNBS, colitis, Crohn's disease, animal model. Two investigators independently reviewed the abstracts and appropriate articles were included in this review. The aim of this study was to thoroughly present an updated review of the TNBS-induced colitis protocols that are implemented by researchers.